FACTORS THAT ENCOURAGE MELAYU PEOPLE TO FOLLOW THE SYATTARIYYAH TARIKAT OF SYEKH H. ABDURRAHMAN SILAU LAUT - Syukri Syukri; Sulaiman Muhammad Amir; Safria Andy (State Islamic University of North Sumatra Indonesia, 2020)
The study of Malays, is inseparable from their beliefs and concerns about the teachings of Islam. But does every Malay person want to enter the tarikat, specifically the Syattariyah Tarikat Mr. Sheikh H. Abdurrahman Silau Laut. If so, what factors drove them to enter it? Therefore, this paper focuses on in-depth interviews (dept interview), using the